Manejo y aprovechamiento ecoturístico del humedal la tembladera ubicado en el sitio San José del cantón Santa Rosa en el año 2014. - Rivera Ojeda, Edinson Rubén (2015)
In order to assist with the care of the environment, the improvement of communities and the interaction between the university and society, this research project , structured by students studying Environmental Management at the Technical University of Machala presents .